ОД ФОНОТАКТИКАТА НА МАКЕДОНСКИОТ ЈАЗИК (Филолошки студии, 2019)
The subject of analysis in this article is assimilation of voice in Macedonian: in cases of contact between obstruents with different voice features (within the word or at word boundaries), voicing and devoicing of obstruents, or regressive sandhi, oc- curs. But this rule does not apply to /v/ because this obstruent allows both progres- sive assimilation (for example [sfet], [sfat], [sfaca], [sfeca], [sfari], [sfekor], [sfekrva]) and regressive assimilation before a sonant in inflectional morphemes for imperfect and aorist ([imafme], [dojdofme]). In the phonetic system of some Western Macedonian dialects there is no voiceless fricative /f/ and in past tense inflections a voiced /v/ is pronounced ([imavme] / [imavne], [bevme]/ [bevne], etc.). As far as the sandhi in final position is concerned, a few characteristics should be pointed out. Final obstruents are often voiceless before initial voiced obstruents ([ubaf graf si kupil], [so blagoslof za bericet]), although obstruents remaining un- changed is also a regular feature ([Belov gi posakuva] [ Belov bese…] [takov zakon], [sakav da kaèam], [izlez od drèavata]). Final voiced consonant is also devoiced if followed by a word with initial sonant or vowel ([nadvor ot periot na kampaÜa], [Belgrat izrazuva...], [upravniot sut ja poniʃti..], [snek na planinite], etc.). In Macedonian, there is a new tendency to keep voiced obstruents in final position or before a long break ([izlez], [vlez], [prihod], [red], [sud], [strav], [izgrev], [l'ubov], [potsmev], [ekskluziv] [adev], [nosev], [piev]) especially in words with final /v/. This kind of pronunciation can be attributed to the influence of orthogra- phy, but we cannot exclude the influence of the neighbouring languages, such as Serbian, for example, a Slavic language without sandhi.
Keywords: orthoepy, pronunciation, sandhi, assimilation, obstruents, voiced obstruents, voiceless obstruents, sonants, vowels.